Visualising the ‘Big Ship’; The reconstruction of a 12th-century cargo vessel found in the harbour of Wismar - Auer, Jens; Ditta, Massimiliano (Sailing through History. Reading the Past – Imagining the Future: Proceedings of the 16th International Symposium on Boat & Ship Archaeology ISBSA 16, 2024)
At the ISBSA 15 in Marseille, the authors presented the preliminary results from the excavation of a Medieval cargo vessel in the port of Wismar (Germany), built from oak and pine sourced from western Sweden in the period AD 1184-1190. Since then, the full documentation of the wreck has been completed, and the timbers are currently undergoing conservation treatment. As the next step, a minimum reconstruction of the hull form was carried out to analyse the ship’s design and construction. This paper discusses the methodology used for the archaeological reconstruction and presents the results of the hull analysis. Finally, the Wismar ship is compared with contemporary ship finds intending to explore its place in the development of the sailing cargo vessel in the 12th and 13th centuries.